BioHastalex modified with silver nanolayers and heat treatment for antibacterial properties - Nikola Slepičková Kasálková; Silvie Rimpelová; Cyril Vacek; Bára Frýdlová; Iva Labíková; Jan Plutnar; Kamil Severa; Václav Švorčík; Petr Slepička (Heliyon)
Here, we present surface analysis and biocompatibility evaluation of novel composite material based on graphene oxide traded as BioHastalex. The pristine material's surface morphology and surface chemistry were examined by various analytical methods. The BioHastalex with a thin silver layer was subsequently heat treated and characterized, the impact on the material surface wettability and morphology was evaluated. Significant surface roughness and morphology changes were detected at the nanometer scale after heat treatment of Ag-sputtered BioHastalex. The deposition of a thin silver nanolayer had an outstanding effect on BioHastalex's antibacterial properties while still maintaining cell viability (MRC-5, HaCaT). The heat treatment of BioHastalex-Ag led to the formation of regular nanocluster arrays while affecting the Ag concentration on the very surface. The decrease in silver concentration was connected with the length of heat treatment; cells growing on such samples exhibited good viability, and the antibacterial properties were weaker than simply sputtered BioHastalex.